2014
DOI: 10.1038/ncomms6241
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis is regulated via microRNA-200/ZEB1 axis control of tumour cell PD-L1 expression and intratumoral immunosuppression

Abstract: Immunosuppression of tumor-infiltrating lymphocytes (TIL) is a common feature of advanced cancer, but its biological basis has remained obscure. We demonstrate here a molecular link between epithelial-to-mesenchymal transition (EMT) and CD8+ TIL immunosuppression, two key drivers of cancer progression. We show that microRNA-200 (miR-200), a cell-autonomous suppressor of EMT and metastasis, targets PD-L1. Moreover, ZEB1, an EMT activator and transcriptional repressor of miR-200, relieves miR-200 repression of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
763
5
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 826 publications
(828 citation statements)
references
References 54 publications
39
763
5
1
Order By: Relevance
“…Co-enrichment of these signatures, collectively referred to as the Innate anti-PD-1 Resistance or IPRES signature, again indicated heightened mesenchymal transition, angiogenesis, hypoxia and wound healing. The concurrence of a tumor cell mesenchymal phenotype with an angiogenesis-and wound healing-related inflammatory microenvironment has been documented in the literature (Chen et al, 2015a;Chen et al, 2015b;Mak et al, 2015). Interestingly, this set of 26 IPRES signatures included signatures induced by MAPK inhibitor (MAPKi) treatment of melanoma tumors and cell lines (Table S2C).…”
Section: Co-enriched Transcriptomic Signatures In a Major Subset Of Amentioning
confidence: 91%
“…Co-enrichment of these signatures, collectively referred to as the Innate anti-PD-1 Resistance or IPRES signature, again indicated heightened mesenchymal transition, angiogenesis, hypoxia and wound healing. The concurrence of a tumor cell mesenchymal phenotype with an angiogenesis-and wound healing-related inflammatory microenvironment has been documented in the literature (Chen et al, 2015a;Chen et al, 2015b;Mak et al, 2015). Interestingly, this set of 26 IPRES signatures included signatures induced by MAPK inhibitor (MAPKi) treatment of melanoma tumors and cell lines (Table S2C).…”
Section: Co-enriched Transcriptomic Signatures In a Major Subset Of Amentioning
confidence: 91%
“…Chen et al [131] demonstrated that miR-200 suppressed the epithelial to mesenchymal transition (EMT) process by targeting PD-L1 and thus delaying cancer progression in a mouse model. As shown before, miR-200 expression is downregulated in highly metastatic cancer cells [132,133].…”
Section: Mirnas As Key Modulators Of Tumour Immune Response In Lung Cmentioning
confidence: 99%
“…117,118 Iliopoulos et al 119 demonstrated that miR-21 expression was upregulated by ovalbumin stimulation in T cells and also that the inhibition of PD-1 increased miR-21 expression. Chen et al 120 suggested that a relationship exists between miR-200 and PD-L1 expression in human lung cancer. Furthermore, previous studies have indicated that a relationship exists between these immune checkpoints and a number of miRNA; however, these relationships have not yet been elucidated in detail.…”
Section: Mirna In Triple-negative Breast Cancermentioning
confidence: 99%